Moringa Leaf Cookies: A Nutritious Snack to Prevent Stunting in Sawocangkring Village: Cookies Daun Kelor : Camilan Bergizi untuk Mencegah Stunting di Desa Sawocangkring (Indonesian Journal of Cultural and Community Development, 2024)
Stunting is a global health issue that significantly impacts the growth and development of children, particularly in regions facing nutritional deficiencies. In Sawocangkring Village, there is a pressing need for innovative nutritional interventions. This study aims to utilize moringa leaves in the production of cookies as a nutritious snack solution to combat stunting. The community service program was designed with distinct stages, including preparation, implementation, and evaluation, employing observation techniques to assess community engagement. The activity centered on developing moringa leaf cookies while monitoring the community's acceptance of the product. The findings indicate that these cookies not only enhance the nutritional value of snacks but are also positively received by the local population. The novelty of this initiative lies in integrating moringa leaves into a familiar food product, thereby promoting both health benefits and local agricultural resources. The implications of this program suggest that the sustainable production of moringa leaf cookies could serve as a viable livelihood strategy for the community, while also contributing to the broader effort of reducing stunting through improved nutrition.Highlights:• Moringa leaf cookies enhance nutritional value, addressing stunting in children.• The community service program involved preparation, implementation, and evaluation stages, fostering local engagement.• Positive community acceptance suggests potential for sustainable production as a livelihood strategy.Keywords: Stunting, moringa leaves, cookies, nutrition, community service.